(untitled) (Medical Forum Monthly, 2024)
Objective: To describe the socio-demographic along with the medico-legal characteristics of rape assailants and victims reporting to a police station in Rawalakot, Azad Kashmir. Study Design: Retrospective study. Place and Duration of Study: This study was carried out at Forensic Medicine Department, Poonch Medical College, Rawalkot Jan 2007 to April 2015. Materials and Methods: This was a retrospective cohort study in which a total of 67 cases of alleged rape victims were identified while reviewing all available police files concerning reported rapes and attempted rapes from 2007 to 2015.The data was gathered on preformed questionnaires after conducting the pilot study. All information about victims and alleged offenders were extracted from the police files including socio-demographic profile of the both the accused and victim i.e age of the victim and assailant, marital status of assailant and victim, time of incident, number of accused persons and whether challan was filed or otherwise. Results: A total of 67 cases were collected from the police records regarding the alleged rape cases. Maximum number of victims belonged to age group of 21 to 30 years and most offenders also belonged to same age group. 70.1%(n=47 of victims and 79.1%(n=53) of assailants were unmarried. In most of the cases, one offender was involved while gang rape constituted 6%(n=4) of cases. Most cases were reported between 1200-1800 Hrs followed by 0600-1200 Hrs. The total no of cases year wise are 4 in 2007, 4 in 2008, 7 in 2009, 5 in2010,13 in 2011,5 in 2012,11 in 2013,13 in 2014 and 5 in first 4 months of 2015.